The Sanctity of Rural Life : Nobility, Protestantism, and Nazism in Weimar Prussia. - Baranowski, Shelley (Oxford University Press, 1995)
This is a study of rural social relationships in the eastern Prussian provinces during the Weimar Republic. Using the province of Pomerania as its primary example, it assesses the contributions of rural elites, particularly Junker landlords and Protestant clergymen.